Dilepton production with the SMASH model. (August 2016) - Weil, Janus; Staudenmaier, Jan; Petersen, Hannah
Abstract: In this work the SMASH model is presented ("Simulating Many Accelerated Strongly-Interacting Hadrons"), a next-generation hadronic transport approach, which is designed to describe the non-equilibrium evolution of hadronic matter in heavy-ion collisions. We discuss first dilepton spectra obtained with SMASH in the few-GeV energy range of GSI/FAIR, where the dynamics of hadronic matter is dominated by the production and decay of various resonance states. In particular we show how electromagnetic transition form factors can emerge in a transport picture under the hypothesis of vector-meson dominance.